Sistem Pendataan Barang Material Masuk dan Keluar (Studi Kasus: PT. QTON Indonesia) - Dewi Yohana Br. Ginting; Melvarina Tamba; Wulandari (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
the internet is possible for every employee to communicate via e-mail and even interact directly by using a teleconference or videoconferencing. To be able to provide accurate, fast, and accurate information, companies need a quality digital-based information system. This desire is based on irregular and less effective processing of company data, which can be a tool that is not only able to provide information, but is also able to process information because the company's database has many advantages such as large data capacity, easy data retrieval. , faster in the process of making reports and more efficient and effective. The design of an inventory information system at PT. QTON Indonesia to make it easier for the warehouse and purchasing departments to provide reports to the leadership and Applications. Data processing systems can also be used to help minimize the error rate that usually occurs in semi-computerized systems.